Memorandum of Understanding between the Ministry of Food and Disaster Management, CDMP and BRAC University for Knowledge and Resource Sharing on Disaster Management Issues (2009) - Comprehensive Disaster Management Programme (CDMP); BRAC University (Comprehensive Disaster Management Programme (CDMP) and BRAC University, 2013)
Memorandum of Understanding between the Ministry of Food and Disaster Management Comprehensive Disaster Management Programme (CDMP) and BRAC University, Dhaka Bangladesh for Knowledge and Resource Sharing on Disaster Management Issues.